Accumulation of the bitter substance quercetin mediated by the overexpression of a novel seed-specific gene FtRDE2 in Tartary buckwheat - Zhao, Haixia (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 Elsevier Masson SAS. All rights reserved.